Representações de Damiana da Cunha na história e na literatura - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The search "Historical and literary representations of Damiana da Cunha" focuses the representations that have been built over the centuries XIX, XX and XXI, in historiography and literature. Damiana da Cunha is within the context of Goiás history marked by the occupation of the territory and the extermination of indigenous peoples who lived here; this indigenous belonged to the South Kayapo ethnic group, which resisted until the late eighteenth century to the appropriation of their territory. With Pombalina Indian policy of assimilation of the Indians, the Southern Kayapó were villagers in the 1780s, a period that corresponds to the "projection" of Damiana da Cunha (1780-1831). Documents, travelers' accounts, historical and literary narratives show the Damiana da Cunha acting and the roles she played on the current Indian policy. However, the representations built on Damiana da Cunha, especially the biographies of the nineteenth century and early twentieth century, were characterized by the approach to the national project designed by the state, which, among other things, emphasize the "beneficial" results of colonization; the creation of myths and national heroes; the inclusion of the indigenous in historiographical and literary production; among others. Damiana da Cunha is represented as a missionary heroine, converted to Christianity, who sacrificed her life for "love" to her people and colonial and imperial service management, that is, in favor of "collective good". The goiana literature in the twentieth century also represented Damiana da Cunha and analyzed her behavior guided in non- indigenous culture; the analysis of these representations show a heroin and virtuous Damiana da Cunha, that is, the prototype of a heroic vision inherent in the nineteenth century national project. The disjuption with this view was presented at novel Guerra no Coração do Cerrado by Maria Jose Silveira, published in 2006. The work addresses Damiana da Cunha from the ambiguity of life between the two worlds, the indigenous and non-indigenous; and analyzes her (re) oncoming with the Kayapo South in the cultural and social spheres.
Keywords: Damiana da Cunha; Kayapó do Sul; Goiás; História; Literatura; Damiana da Cunha; South Kayapó ethnic group; Goias; History; Literature; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::ANTROPOLOGIA; LETRAS::LITERATURA BRASILEIRA